The potential of 3-dimensional construct engineered from poly(lactic-co-glycolic acid)/fibrin hybrid scaffold seeded with bone marrow mesenchymal stem cells for in vitro cartilage tissue engineering - Abdul Rahman, Rozlin; Mohd Shukri, Norhamiza; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa'zamuddin; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin; Hashi, Abdurezak Abdulahi; Abdul Rahman, Suzanah; Sha'ban, Munirah (Elsevier, 2015)
Articular cartilage is well known for its simple uniqueness of avascular and aneural structure that has limited capacity to heal itself when injured. The use of three dimensional construct in tissue engineering holds great potential in regenerating cartilage defects. This study evaluated the in vitro cartilaginous tissue formation using rabbit's bone marrow mesenchymal stem cells (BMSCs)-seeded onto poly(lactic-co-glycolic acid) PLGA/fibrin and PLGA scaffolds. The in vitro cartilaginous engineered constructs were evaluated by gross inspection, histology, cell proliferation, gene expression and sulphated glycosaminoglycan (sGAG) production at week 1, 2 and 3. After 3 weeks of culture, the PLGA/fibrin construct demonstrated gross features similar to the native tissue with smooth, firm and glistening appearance, superior histoarchitectural and better cartilaginous extracellular matrix compound in concert with the positive glycosaminoglycan accumulation on Alcian blue. Significantly higher cell proliferation in PLGA/fibrin construct was noted at day-7, day-14 and day-21 (p < 0.05 respectively). Both constructs expressed the accumulation of collagen type II, collagen type IX, aggrecan and sox9, showed down-regulation of collagen type I as well as produced relative sGAG content with PLGA/fibrin construct exhibited better gene expression in all profiles and showed significantly higher relative sGAG content at each time point (p < 0.05). This study suggested that with optimum in vitro manipulation, PLGA/fibrin when seeded with pluripotent non-committed BMSCs has the capability to differentiate into chondrogenic lineage and may serve as a prospective construct to be developed as functional tissue engineered cartilage.